Hormonal Contraception Temporarily Suppresses Ovarian Reserve Markers with Partial Recovery - Noor Salman Dalis; Bashaer Ibrahim Hamdi; Raad Fadhil Abdullah Yosef (Academia Open, 2026)
General Background: Hormonal contraception is widely used, yet its implications for ovarian reserve markers remain debated. Specific Background: Cross-sectional studies report lower anti-Müllerian hormone (AMH) and antral follicle count (AFC) among users, but lack baseline data to determine temporal dynamics and reversibility. Knowledge Gap: Prospective evidence with serial baseline and follow-up measures comparing contraceptive methods is limited. Aims: This study prospectively evaluated longitudinal changes in AMH, AFC, and follicle-stimulating hormone among women initiating combined oral contraceptives or levonorgestrel-releasing intrauterine devices versus non-users. Results: Mixed-effects models demonstrated significant time-by-group interactions, with early declines in AMH and AFC at three months, followed by partial recovery during continued use, while controls remained stable. Novelty: By integrating baseline and repeated measures, this study delineates functional, time-dependent suppression rather than structural ovarian damage. Implications: Findings support counseling that hormonal contraception induces temporary, reversible alterations in ovarian reserve markers and should not be interpreted as permanent fertility impairment.Keywords : Hormonal Contraception, Anti-Müllerian Hormone, Ovarian Reserve Markers, Longitudinal Cohort Study, Oral ContraceptivesHighlight : AMH levels decreased 25-29% at 3 months, then partially recovered by 12 months Changes reflect temporary ovarian suppression, not permanent structural damage to ovaries Both OCP and LNG-IUD users showed similar suppression and recovery patterns